Veolia to build, operate water treatment plant for Antero Resources. Issue 10 (October 2015) - Unknown
Abstract : Antero Resources, a producer of oil & natural gas in the Marcellus and Utica Shale plays, has selected Veolia Water Technologies and Veolia North America to design, build and operate a US$275 million treatment complex in West Virginia.